PENGARUH KEGIATAN MEMBATIK MENGGUNAKAN TEKNIK ECOPRINT TERHADAP KEMAMPUAN KREATIVITAS PADA ANAK USIA 5-6 TAHUN DI RA NURUL ITTIHADIYAH - Khairani Ulfa; Juli Yanti Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to determine the effect of batik making activities using ecoprint techniques on creativity in children aged 5-6 years at RA Nurul Ittihadiyah. The type of sample selection used by researchers is the Non-Probability Sampling type, namely saturated sampling. The type of research used is a quantitative method with One Group PreTest-Posttest design using batik activities using ecoprint techniques. The research instruments and data collection techniques used were checklists and documentation. Based on the results of data analysis in the normality test via the Shapiro-Wilk test results, the two variables (PreTest and PostTest) have a statistically normal distribution. The Shapiro-Wilk statistical value for the PreTest is 0.809 with a significance value (p) = 0.071, while for the PostTest it is 0.881 with a significance value (p) = 0.088. Because both p values ​​are greater than 0.05, it can be concluded that the data is normally distributed, thus the hypothesis Ho is rejected and Ha is accepted. So it can be stated that there is a significant influence of batik making activities using ecoprint techniques on creativity in children aged 5-6 years at RA Nurul Ittihadiyah